2021
DOI: 10.1128/mbio.00863-21
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genomic and Biochemical Analysis Reveals Pleiotropic Effect of Congo Red on Aspergillus fumigatus

Abstract: Inhibition of fungal growth by Congo red (CR) has been putatively associated with specific binding to β-1,3-glucans, which blocks cell wall polysaccharide synthesis. In this study, we searched for transcription factors (TFs) that regulate the response to CR and interrogated their regulon. During the investigation of the susceptibility to CR of the TF mutant library, several CR-resistant and -hypersensitive mutants were discovered and further studied. Abnormal distorted swollen conidia called Quasimodo cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 89 publications
1
29
0
Order By: Relevance
“…We found clear and reproducible reduction in the level of AbcG1 in strains lacking either the atrR or AFUB_026340 ( Afu2g10550 ) gene. The latter gene has recently been characterized as a locus enhancing expression of genes involved in fermentation (favors fermentative metabolism, ffmA [ 19 ]), and we will use this designation here. The ffmA gene has also been characterized as rfeC (regulator of FLO11 ) on the basis of activating the FLO11 promoter when expressed as a cDNA clone in Saccharomyces cerevisiae ( 22 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found clear and reproducible reduction in the level of AbcG1 in strains lacking either the atrR or AFUB_026340 ( Afu2g10550 ) gene. The latter gene has recently been characterized as a locus enhancing expression of genes involved in fermentation (favors fermentative metabolism, ffmA [ 19 ]), and we will use this designation here. The ffmA gene has also been characterized as rfeC (regulator of FLO11 ) on the basis of activating the FLO11 promoter when expressed as a cDNA clone in Saccharomyces cerevisiae ( 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…More detailed analysis of the phenotype of a ffmAΔ strain clearly indicated that loss of this gene had a modest azole drug phenotype compared to its pronounced defect in growth. Other screenings of this transcription factor deletion mutant library led to the detection of ffmA as a determinant required for resistance to cell wall stress agents but also showed a very similar general growth defect ( 19 ). Based on both this and the previous study of the phenotype of the ffmAΔ strain, it seems that the primary phenotype caused by loss of ffmA is a severe growth deficit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore spotted cells of the WT strain, the grx4Δ mutants and the complemented strain onto YPD media supplemented with SDS, Congo Red, caffeine, or CFW. The detergent SDS disrupts the plasma membrane, whereas CFW and Congo Red interfere with the synthesis of cell wall polysaccharides ( Elorza et al 1983 ; Wood and Fulcher 1983 ; Dichtl et al 2016 ; Liu et al 2021 ). Caffeine has a variety of targets in fungi including target of rapamycin (TOR) signaling and components of the CWI pathway ( Ruta and Farcasanu 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, CFW and CR are thought to act by binding to chitin and β-linked-glucan chains, thereby inhibiting the assembly of chitin and β-linked-glucans and weakening the cell wall [ 114 ]. Recently, several transcription factors involved in CR sensitivity and CR dynamics in fungal cells have been analyzed [ 116 ]. The amorphous cell surface polysaccharide, galactosaminogalactan (GAG), interferes with the uptake of CR into the fungal cell [ 116 ].…”
Section: Cell Wall Integrity As a Drug Target For Antifungal Agentsmentioning
confidence: 99%